A high heterozygosity genome assembly of Aedes albopictus enables the discovery of the association of PGANT3 with blood-feeding behavior - Deng, Yuhua; Ren, Shuyi; Liu, Qiong; Zhou, Dan; Zhong, Caimei; Jin, Yabin; Xie, Lihua; Gu, Jinbao; Xiao, Chuanle (BMC genomics, 2024)
The Asian tiger mosquito, Aedes albopictus , is a global invasive species, notorious for its role in transmitting dangerous human arboviruses such as dengue and Chikungunya. Although hematophagous behavior is repulsive, it is an effective strategy for mosquitoes like Aedes albopictus to transmit viruses, posing a significant risk to human health. However, the fragmented nature of the Ae. albopictus genome assembly has been a significant challenge, hindering in-depth biological and genetic studies of this mosquito. In this research, we have harnessed a variety of technologies and implemented a novel strategy to create a significantly improved genome assembly for Ae. albopictus , designated as AealbF3. This assembly boasts a completeness rate of up to 98.1%, and the duplication rate has been minimized to 1.2%. Furthermore, the fragmented contigs or scaffolds of AealbF3 have been organized into three distinct chromosomes, an arrangement corroborated through syntenic plot analysis, which compared the genetic structure of Ae. albopictus with that of Ae. aegypti . Additionally, the study has revealed a phylogenetic relationship suggesting that the PGANT3 gene is implicated in the hematophagous behavior of Ae. albopictus . This involvement was preliminarily substantiated through RNA interference (RNAi) techniques and behavioral experiment. In summary, the AealbF3 genome assembly will facilitate new biological insights and intervention strategies for combating this formidable vector of disease. The innovative assembly process employed in this study could also serve as a valuable template for the assembly of genomes in other insects characterized by high levels of heterozygosity.